2008
DOI: 10.1007/s10593-009-0194-x
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of 3-nitro-1,2,4-triazoles with alkylating agents. 6*. Alkylation of a neutral heterocycle by alcohols in acid media*

Abstract: The physicochemical properties of N-substituted 3-nitro-5-R-1,2,4-triazoles are markedly affected by the positioning and type of substituent on the cyclic nitrogen atoms [2][3][4][5].The development of directed methodology for the synthesis of N-substituted azoles and the search for conditions activating all three nitrogen atoms in the reactions of monofunctionalization of nitrotriazoles are important problems in basic and applied science. On the one hand it contributes to deciding one of the key challenges in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Street 38 and Del Giudice 47 reported that with NaH as alkaline medium the two regioisomers N 1 and N 2 were prevalently obtained, while the N 4 methylation was not very easy to realize in these conditions. 48,49 In our synthetic procedure (NaH/DMF/MeI), as expected, a mixture of two isomers in a ratio of about 3/1 (assigned by NCH 3 peaks at 4.051 and 4.153 ppm in 1 H NMR spectroscopy) was recovered and only one was obtained as pure product (isomer with the NCH 3 signal at 4.051 ppm) by crystallization. Unfortunately, an X-ray analysis was not performed because unsuitable crystals were obtained and it was impossible to assign the isomer structure using only 1 H NMR spectroscopy.…”
Section: Mrk-016supporting
confidence: 64%
“…Street 38 and Del Giudice 47 reported that with NaH as alkaline medium the two regioisomers N 1 and N 2 were prevalently obtained, while the N 4 methylation was not very easy to realize in these conditions. 48,49 In our synthetic procedure (NaH/DMF/MeI), as expected, a mixture of two isomers in a ratio of about 3/1 (assigned by NCH 3 peaks at 4.051 and 4.153 ppm in 1 H NMR spectroscopy) was recovered and only one was obtained as pure product (isomer with the NCH 3 signal at 4.051 ppm) by crystallization. Unfortunately, an X-ray analysis was not performed because unsuitable crystals were obtained and it was impossible to assign the isomer structure using only 1 H NMR spectroscopy.…”
Section: Mrk-016supporting
confidence: 64%
“…In particular, Saraev et al [11] reported on their selective alkylation at N 1 with adamantan-1-ol and tert-butyl alcohol in sulfuric acid, whereas the alkylation with isopropyl alcohol afforded exclusively the corresponding N 2 -derivative [12]. The observed regioselectivity may be interpreted in terms of weakly basic properties of triazoles which undergo protonation at the most basic nitrogen atom.…”
mentioning
confidence: 99%
“…Predominant formation of isomer IIa is likely to be determined by protonation of initial triazole I in sulfuric acid with formation of 3-nitro-1H-1,2,4-triazol-4-ium cation where only the N 2 atom is accessible to attack by the cation generated from allyl bromide. This mechanism was recently proposed to rationalize selective alkylation of triazole (I) with tert-butyl alcohol [12] and was based on the data for selective acidcatalyzed N 2 -alkylation of tetrazoles as structural analogs of I [15]. Isomeric products IIb and IIc may be formed as a result of electrophilic attack on unprotonated 3-nitro-1,2,4-triazole species present in the reaction mixture at a small concentration.…”
mentioning
confidence: 99%
“…Selectivity of alkylation of NRT is observed only in exceptional cases on using special conditions, such as on alkylating NRT with alcohols in a medium with enhanced acidity, providing complete protonation of the nitrotriazole ring at the most basic N(4) position [12,13]. On interacting NRT in an acidic medium with alcohols, the structure of which aid stabilization to a definite degree of the carbocations formed from them, alkylation occurs at atom N(2).…”
mentioning
confidence: 99%
“…On interacting NRT in an acidic medium with alcohols, the structure of which aid stabilization to a definite degree of the carbocations formed from them, alkylation occurs at atom N(2). However, as a result of the inclination of certain N(2) isomers to isomerize (for example, 2-isobutyl-and 2-tert-butyl-5-nitro-1,2,4-triazoles) their complete or partial transformation into the corresponding N(1) isomers frequently occurs under the reaction conditions [12,13].…”
mentioning
confidence: 99%